'Not everybody walks around and thinks "That's an example of othering or stigmatisation"': Identity, pedagogic rights and the acquisition of undergraduate sociology-based social science knowledge. (July 2015) - McLean, Monica; Abbas, Andrea; Ashwin, Paul
This article places itself in conversation with literature about how the experience and outcomes of university education are structured by intersections between social class, ethnicity, gender, age and type of university attended. It addresses undergraduate students' acquisition of sociological knowledge in four diverse university settings. Basil Bernstein's concepts of pedagogic identity, pedagogic rights, classification and framing are employed to analyse curriculum and interviews with 31 students over the period of their undergraduate degree. The nature of a sociology-based disciplinary identity is described and illustrated, and it is shown how the formation of this identity gives access to pedagogic rights and the acquisition of valuable capabilities. Addressing the question of whether pedagogic rights are distributed unequally in a stratified university system, it was found that they were not distributed, as might be expected, according to institutional hierarchy. It is argued that the acquisition of university sociological knowledge can disrupt social inequality.